MOUNT SINABUNG DISASTER MITIGATION CHALLENGES AND STRATEGIES TO IMPROVE COMMUNITY SUSTAINABILITY - Hariani, Riri Rezeki; Badaruddin; Ginting, Bengkel (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This research aims to study how disaster mitigation challenges and strategies by governments in employment improve community sustainability. This type of research is qualitative. Data collection techniques use interview guidelines. Data processing and analysis are carried out with stages of data reduction, data presentation and conclusion-making, and then the data is analyzed qualitatively. The results of this study suggest that the main challenges and constraints in current disaster mitigation efforts include inadequate early warning systems, limited evacuation routes and facilities, insufficient resources for disaster preparedness, and gaps in public awareness and readiness. While community sustainability strategies are expected to be able to propose strategies to improve the sustainability of communities in the face of volcanic hazards, these strategies may include improving early warning systems, improving evacuation planning and infrastructure, enhancing community-based disaster preparedness initiatives, strengthening collaboration between government agencies, NGOs, and local communities, and integrating traditional knowledge